Imaging of Blunt Pancreatic Trauma: A Systematic Review. Issue 3 (August 2020) - Odedra, Devang; Mellnick, Vincent M.; Patlas, Michael N.
Purpose: Despite several published reports on the value of imaging in acute blunt pancreatic trauma, there remains a large variability in the reported performance of ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI). The purpose of this study is to present a systematic review on the utility of these imaging modalities in the acute assessment of blunt pancreatic trauma. In addition, a brief overview of the various signs of pancreatic trauma will be presented. Methods: Keyword search was performed in MEDLINE, EMBASE, and Web of Science databases for relevant studies in the last 20 years (1999 onward). Titles and abstracts were screened, followed by full-text screening. Inclusion criteria were defined as studies reporting on the effectiveness of imaging modality (US, CT, or MRI) in detecting blunt pancreatic trauma. Results: After initial search of 743 studies, a total of 37 studies were included in the final summary. Thirty-six studies were retrospective in nature. Pancreatic injury was the primary study objective in 21 studies. Relevant study population varied from 5 to 299. Seventeen studies compared the imaging findings against intraoperative findings. Seven studies performed separate analysis for pancreatic ductal injuries and 9 studies only investigated ductal injuries. The reported sensitivities for the detection of pancreatic injuries at CT ranged from 33% to 100% and specificity ranged from 62% to 100%. Sensitivity at US ranged from 27% to 96%. The sensitivity at MRI was only reported in 1 study and was 92%. Conclusion: There remains a large heterogeneity among reported studies in the accuracy of initial imaging modalities for blunt pancreatic injury. Although technological advances in imaging equipment would be expected to improve accuracy, the current body of literature remains largely divided. There is a need for future studies utilizing the most advanced imaging equipment with appropriately defined gold standards and outcome measures.